The Role of Sports Activities in Reducing Aggressive Behavior (Physical and Symbolic) for 12-year-old Pupils in Izz al-Din al-Qassam School (Experimental Study) - ديوب, نائل (Latakia University Journal -Medical Sciences Series, 2024)
The current study dealt with the disclosure of the role of sports activities that included a group of recreational and interesting group games in reducing the aggressive behavior (physical and symbolic) of 12-year-old pupils in Izz al-Din al-Qassam School in the city of Jableh, affiliated to the Directorate of Education in Lattakia Governorate. The quasi-experimental approach was followed. The study sample consisted of (24) pupils divided into two groups: the first was an experimental group consisting of (12) students, and the second was a control group consisting of (12) students. The scale of aggressive behavior used was (Al-Amayrah, 1991), and the construction of the sports activities program, which consisted of (20) sessions, (45) minutes each. The results showed that the students of the experimental group showed a decrease in aggressive behavior, compared to the control group that did not show a decrease in aggressive behavior. The study recommended a program of sports activities to reduce physical aggressive behavior among 12-year-old students.